The Effect of Project Management Functions Related to Cost, Quality, and Time on the Success of Road Condition Survey Projects Case Study: Survey of Road and Bridge Conditions By the North Sulawesi Regional Public Works Office - Michelle Angelita Monica Karundeng; Steenie E. Wallah; Ariestides K. T. Dundu (CV. Publikasi Indonesia, 2026)
This study examines the influence of project management functions on the success of road and bridge condition survey work at the National Road Implementation Agency (BPJN) of North Sulawesi. The research focuses on four management functions—planning, organizing, implementation, and control—measured through cost, quality, and time indicators. A quantitative approach was applied using questionnaire data collected from consultants involved in the BPJN North Sulawesi Road and Bridge Condition Survey project. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that all four management functions have a positive and significant effect on survey work success. The implementation function shows the strongest influence, followed by control, organizing, and planning functions. The R-square value of 0.682 indicates that 68.2% of the variation in survey work success can be explained by the four management functions, while the remaining 31.8% is influenced by other factors outside the model. The Q-square value of 0.439 confirms that the model has good predictive relevance. These findings highlight the importance of effective implementation, cost monitoring, quality control, time efficiency, and adaptive field management in improving the success of road condition survey projects. Therefore, strengthening project management practices is essential to ensure accurate, accountable, timely, and budget-efficient survey outcomes.